Game-Based Learning and its Role in Boosting Students’ Motivation and Academic Achievement (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Game-based learning, an instructional approach that integrates interactive games to enhance student engagement and learning outcomes, has gained increasing attention for its potential to improve motivation and academic performance. This study examined the role of game-based learning in enhancing students’ motivation and academic achievement among Key Stage 2 learners in the District of Wright I, Schools Division of Samar, during School Year 2025–2026. Using a quantitative descriptive-correlational research design, the study explored relationships among students’ profile variables, perceptions of game-based learning implementation, motivation, and academic performance. Findings revealed that most students demonstrated moderately high academic performance, with 67.14 % achieving mean grades between 85 and 89. Among the profile variables, only access to gadgets at home and positive attitudes toward game-based learning were significantly correlated with perceived implementation and motivation, while age, sex, and frequency of gadget use showed no significant relationships. Student and teacher perceptions of implementation were not significantly associated with academic achievement, although positive learning attitudes showed a weak relationship with slightly higher performance. Teachers identified difficulty in clarifying instructions and rules as a major implementation challenge. Recommendations include enhancing teacher training, improving access to technology, fostering positive learning attitudes, and conducting further studies on long-term outcomes.